Kompetensi Pengetahuan Dan Teknik Penilaian Tindakan Kelas Di Sekolah Dasar - Rizki Zuliani; Aprilia Azzahra; Diana Khoirun Nisa’ (CV. ITTC INDONESIA, 2023)
Assessment is the process of collecting and processing information to measure the achievement of student learning outcomes. The process is carried out through various assessment techniques, using various instruments, and comes from various sources to be more comprehensive. This research uses a qualitative descriptive approach, which is research that prioritizes data collection or the reality of the problem based on the disclosure of data revealed by informants and written or spoken words from people or observed behavior with actual reality. The results of this study found that the process of obtaining assessments on students there are 2 (two) types of test techniques consisting of, description (essay) and objective tests. In taking assessments on students can be carried out on an ongoing basis to monitor the process of progress, improvement of results in the form of daily tests, midterm tests, semester tests, class promotion tests.